PERBANDINGAN PEMBERIAN BUFFERED PEHAKAIN DENGAN FRESHLY MIXED LIDOKAIN- EPINEFRIN PADA PERSEPSI NYERI KARENA INFILTRASI ANESTESI LOKAL - Ratih Pramuningtyas (Universitas Muhamadiyah Surakarta, 2012)
Over the last decade, there has been a rise in the number of surgical procedures being perfomed under local anethesia. The infiltration of the local anesthetic is the most painful part of this procedures, and pain associations can develop into avoidance behaviors in future procedures. Several techniques were used to reduce the pain of local anesthetic infiltration. The objective of this study is comparing the effect of Buffered Pehacaine versus freshly mixed lidocaine-epinephrin in reducing the pain of local anesthetic infiltration. Six subject were recruited for this study. Each subject was received 2 kind of treatment. Subject rated pain using Visual Analog Score. Pain score were compared using paired t test. Sixty seven percent (67%) subjects reported that pain of infiltration was lower in Buffered pehacaine than freshly mixed lidocaine-epinephrine. The difference was not statistically significant. There are no significant difference between Buffered Pehacaine versus freshly mixed lidocaine-epinephrin in reducing the pain of local anesthetic infiltrationKeywords : local anesthetic infiltration, lidocaine, pehacaine